2009
DOI: 10.1007/s10384-009-0658-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of botulinum a toxin injection on the extraocular muscle fiber layers: Comparison between subtenon injection and intramuscular injection

Abstract: Subtenon injection of botulinum A toxin induced similar morphological changes as direct intramuscular injection in the extraocular muscle fiber layers. These results suggest the possibility of clinical applications of subtenon botulinum A toxin injection for the treatment of strabismus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…23 Although botulinum toxin type A is often used as an alternative to eye muscle surgery for the treatment of strabismus, some morphological studies on extraocular muscles suggest that botulinum toxins induce ultrastructural changes in the myotendinous nerve endings and that these changes might diminish the proprioceptive abilities of the extraocular muscle. 67,68 Corsi et al 69 and Li and Shen 70 noted alterations in the receptor morphology while analyzing resected rectus muscle specimens from patients who had undergone surgery for concomitant strabismus. They suggested that deranged proprioceptive function contributed to the cause of the strabismus.…”
Section: Palisade Endingsmentioning
confidence: 99%
“…23 Although botulinum toxin type A is often used as an alternative to eye muscle surgery for the treatment of strabismus, some morphological studies on extraocular muscles suggest that botulinum toxins induce ultrastructural changes in the myotendinous nerve endings and that these changes might diminish the proprioceptive abilities of the extraocular muscle. 67,68 Corsi et al 69 and Li and Shen 70 noted alterations in the receptor morphology while analyzing resected rectus muscle specimens from patients who had undergone surgery for concomitant strabismus. They suggested that deranged proprioceptive function contributed to the cause of the strabismus.…”
Section: Palisade Endingsmentioning
confidence: 99%
“…This is also extremely rare after botulinum toxin injection with electromyographic guidance [26,27], with an incidence of 0.002% [15]. In rabbits, Paik et al [28] found no different morphologic changes in the extraocular muscle fiber layers between direct intramuscular injection and subtenon injection of botulinum toxin. Therefore, complications after botulinum toxin injection are comparable with and without electromyographic guidance.…”
Section: Plos Onementioning
confidence: 99%
“…This is also extremely rare after botulinum toxin injection with electromyographic guidance [26,27], with an incidence of 0.002% [15]. In rabbits, Paik et al [28] found no different morphologic changes in the extraocular muscle fiber layers between direct intramuscular injection and subtenon injection of botulinum toxin. Therefore, complications after botulinum toxin injection are comparable with and without electromyographic guidance.…”
Section: Plos Onementioning
confidence: 99%